An update on the health benefits promoted by edible flowers and involved mechanisms. (15th March 2021) - Zheng, Jingyun; Lu, Baiyi; Xu, Baojun
Highlights: The health benefits and toxicity of edible flowers were summarized. Anti-oxidant activity, anti-inflammatory, and anti-cancer are main health effects. The health effects of edible flowers were assessed through cell and animal models. Safety levels of edible flowers use for health benefits largely vary. Abstract: The aim of this review is to provide new findings on health effects of edible flowers since 2015. The antioxidant, anti-inflammatory, anti-cancer, hepatoprotective, neuroprotective, anti-diabetic, anti-osteoporosis, anti-obesity, and anti-hypertensive have been reviewed, and the effective concentrations of flower extracts have been summarized. Among all the health benefits mentioned, anti-osteoporosis, anti-obesity, and anti-hypertensive have rarely been mentioned before 2015. Some health benefits mechanisms of edible flowers were discussed frequently after 2015. Some newly found phytochemicals such as polysaccharides were shown to be beneficial to human health. Species of Rosa, Chrysanthemum, and Osmanthus have been reported to exert different health effects on human. For the toxicity studies, the safe level of flower extracts in cell and animal models were at hundreds of parts per million (ppm) level. In consideration of health promoting effects and toxicities of edible flowers, they could serve as potential natural health products for different health benefits.